ANALISIS PENGGUNAAN KATA AJAKAN DALAM MENULIS TEKS PERSUASI PADA SISWA KELAS SMP - Yandis, Siti Muhaya; Pujilestari, Cinta; Wuryani, Woro (IKIP Siliwangi, 2019)
This research is motivated by the problems faced by students in writing persuasion texts, especially on linguistic rules. The distinctive feature of persuasion text is in one of its linguistic rules, namely the invitation word, this study focuses on the type of invitation word, and the purpose is to find out what invitation words are used by persuasion by class VIII students of Annur Lemahabang in writing text. The method used in this study is a qualitative method. The instruments used were in the form of tests and data collection techniques in this study, namely the results of writing persuasion texts of grade VIII students as much as 20. The results of the analysis contained five types of invitations words used by students, (1) the use of invitations to come on the highest percentage is 46%, (2) the next percentage sequence is ayakan invitations word that is as much as 29%, (3) then the next sequence is the word starts as much as 11%, (4) the lowest percentage number shows 7% ie on the word type do it, and (5) keep the word showing the same percentage as the word do that is 7%. These results indicate that the invitation word that is often used by students in writing persuasive texts is the word 'let'.